The System of Educational Quality Management at MIN 2 Sleman Yogyakarta - Munjin Munjin; M. Sugeng Sholehuddin (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2019)
This article will talk about the system of educational quality management implemented at MIN 2 Sleman, Yogyakarta. This issue plays an important role in improving education, especially madrasa. Infact, according to Damayanti (2005:34), our educational level is still low and it really needs improvement as the foundation for an effective partnership among educational institutions. Furthermore, the sense of solidarity and brotherhood seem to decrease as the results of the low character building. In this case, religious institutes seem to have bigger responsibility to solve this problem. The good quality of education in religious institutes (madrassa) will, in turn, produce a generation that is expected to be able to portray himself as the leader of the people, communities and nations. The implementation stages of education quality management at MIN 2 Sleman starts from planning, organizing, mobilizing, supervising, developing and evaluating. The implementation of this phase uses bottom-up, transparent, and accountable system, accompanied by a clear job description in each position so that it can provide optimal education services. The objects of the quality assurance include character building, education, internal audit, teaching learning, and quality development of the teacher and academic staffs. In accordance to the quality assurance, MIN 2 Sleman has implemented Children-Friendly School (CFS) which aims to sett a comfortable shcool for the children, ensure the fulfilment of the right and protection of the children after their own home